Sustainable kenaf/bamboo fibers/clay hybrid nanocomposites: properties, environmental aspects and applications. (1st January 2022) - Jawaid, M.; Chee, Siew Sand; Asim, M.; Saba, N.; Kalia, S.
Abstract: The environmental issues combined with renewability, annual production, valuable characteristics, and low cost have recently generated considerable interest in natural fiber-based hybrid composites. The exceptional mechanical characteristics of fibers can be explored in developing hybrid biocomposites to minimize the risk of environmental hazards. The significant drawbacks of natural fibers are hydrophilic behavior and comparatively high moisture absorption, leading to poor fibre/matrix interfacial bonding and impacting the composite material's final performance. The properties of synthesized fiber-reinforced composites are inconsistent due to the instability in the properties of natural fibers, especially their hydrophilic nature. Another challenge is that poor interfacial bonding due to incompatibility between hydrophobic polymer matrix and hydrophilic fibers. Such problems were addressed by the hybridization effect of natural fibers and inorganic fillers in a polymer matrix. Among various inorganic nanofillers, nanoclay is considered a potential nanofiller for preparing natural fiber-based hybrid nanocomposites. It reduces the effect of moisture to some extent on the mechanical properties of natural fiber-based hybrid composites. This article thoroughly reviews the two important and widely used kenaf and bamboo fibers, covering different mechanical, thermal, and physical properties. This review investigated bamboo and kenaf fiber reinforced thermoset and thermoplastic composites, and nanoclay-based composites. The effect of different nanoclay on mechanical and thermal properties of natural fiber-based hybrid composites is also investigated in detail. Nanoclay-based hybrid composites, especially organically modified MMT, showed improved mechanical properties and better dimensional stability to water absorption and thermal expansion due to strong interfacial adhesion between the OMMT and polymer matrix. Graphical abstract: Image 1 Highlights: This article investigated bamboo and kenaf fiber-based nanoclay hybrid composites. Hybrid composites could deal with the current problem of unsustainable production. The hybridization of fibers with nanoclay improved the properties of polymer composites. The nanoclay-based woven fiber hybrid composites are suitable for automotive parts. Nanoclay-based natural fiber composites have great potential for future research.